Major depressive disorder in multiple sclerosis associated with differences in disease modifying therapy and demographics - Lee, Nathanael J.; Hui, Gavin; Pike, C. William; Galetta, Kristin; Kipp, Lucas B.; Dunn, Jeffrey; Le, Scheherazade; Folmsbee, S. Sai (Frontiers in Neurology, 2025)
Persons with multiple sclerosis (pwMS) are often diagnosed with major depressive disorder (MDD). However, there is a paucity of knowledge regarding the association between different demographic features and such co-diagnosis, as well as the clinical implications the co-diagnosis may carry. This study investigated whether specific demographics demonstrated any correlation with co-diagnosis of MS and MDD, and how MDD comorbidity may potentially impact clinical outcomes. In this single-center study, Black pwMS were more likely to have a MDD comorbidity, and Hispanic pwMS were less likely. MDD comorbidity in pwMS was associated with significantly increased time to disease-modifying therapy (DMT), with the greatest increase in time associated with individuals who received the MDD diagnosis after the MS diagnosis. Among inpatient pwMS, individuals with MDD comorbidity were associated with a decreased usage of MRI while hospitalized. Those who received MDD diagnosis prior to MS were associated with an even further decreased usage of inpatient MRI, and greater mortality. These findings suggest that patient demographics play an important role in how clinicians diagnose MDD in patients with MS. Furthermore, co-diagnosis of MDD may be an important variable that affects healthcare resource utilization and health outcomes.